# algebra

posted by .

Hey, I don't undertand how to solve this equation using substitution.

3y = -1/2x + 2
y= x + 9

• algebra -

sub the 2nd into the 1st

3y = (1/2)x + 2
3(x+9) = (-1/2)x + 2
3x + 27 = (-1/2)x + 2
times 2 to get rid of that nasty fraction

6x + 54 = -x + 4
7x = -50
x = -50/7

then y = x+9 = -50/7 + 9 = 13/7

check:
in #1:
3y = (-1/2)x + 2
LS = 3(13/7) = 39/7
RS =(-1/2)(-50/7) + 14/7
= 25/7 + 14/7 = 39/7 = LS

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### algebra

how do i solve this equation by using substitution?
3. ### Algebra

Solve the system of equations using substitution. x + 4y = -5 3x - 8y = 45 When I tried to solve it, I got x=-17 and y=-3. When I plugged these into the first equation, it didn't work out at all. Could someone please show me the steps …
4. ### algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
5. ### Algebra 1

Using substitution, solve this equation.. 3x - 5y = 11 x - 3y = 1
6. ### College Algebra help!!!

I have to solve each equation using a u substitution and need help understanding how to do this. The first equation is: 1. x^2/3-2x^1/3-15=0 2. x+4=7 Squareroot x+4
7. ### algebra

I have to solve this equation using substitution. 3x+5y=10 2x+ 1/2y=24 This is all one problem
8. ### Algebra Multiple Choice

Hello, This is the last of questions I have for my practice assignment. Again I will put what I got. Thanks for your help. 1.) Solve the system using substitution. Write answer as an ordered pair. 4x+2y=8 -5x-2=y A.) First equation …
9. ### Algebra 1

What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ?
10. ### Math

Solve the integral of (x*e^2x)/(1+2x)^2 by first using u substitution and then use integration by parts. I am very confused on how to do u-substitution with this because no mattter what I let u be equal to the du never comes out to …

More Similar Questions